Data Processing: Information Systems and Technology - Anderson, R. G. (United Kingdom: Longman group, 1987)
This series is divided into eight parts: 1) Information technology. 2) Systems theory. 3) Data. 4) Information. 5) Systems design. 6) Systems selection and installation. 7)Software and hardware; and 8) Information centre and decision support systems.
Includes indexes: p. [281]-287.
ne 21/03/2018
Loan
Keywords: Information technology